Risk Factors of Anesthesia-Related Mortality and Morbidity in One Equine Hospital: A Retrospective Study on 1,161 Cases Undergoing Elective or Emergency Surgeries - Laurenza, Chiara; Ansart, Lèa; Portier, Karine (Frontiers in Veterinary Science, 2020)
A retrospective analysis was performed to determine mortality and morbidity rates for elective and emergency cases in an equine university teaching hospital. It investigated the effect of horse-, anesthetic-, timing and clinician experience-related variables on anesthetic complications. In total, 1161 horses undergoing general anesthesia between January 2012 and December 2016 were included in the study. Patient information and details of the anesthetic, recovery period and immediate complications were retrieved from an archival database. Statistical analysis of qualitative and quantitative factors affecting anesthetic complications was performed using an univariable and multivariable ordinal logistic regression. Odds ratio of variables primarily affecting mortality and complications were calculated. Statistical significance was set at p < 0.05. General anesthesia-related global mortality rate was 1.4% (95% CI [7.1-10.4]) but was only 0.96% (95% CI [0.44-1.82]) for non-colic cases. The complication rate was 17.5% (n=204; 95% CI [15.2-20.0]) of which 46.9% [39.4-54.5] were neuromuscular, 22.6% [16.7-29.5] were respiratory, 15.8% [10.8-22.0] were systemic, 13.6% [8.9-19.5] were cardiovascular, 1.1% [0.1-4.0] were other complications. Ninety two percent of complications occurred during recovery. Major risk factors for mortality and complications included high weight, surgeon experience, increasing age, high ASA score, long duration of anesthesia, quality of induction, lateral recumbency, orthopedic surgery, and hypotension. In these models, colic surgery did not influence the rate of any complications.